2019
DOI: 10.1097/spv.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Pelvic Organ Prolapse Symptoms Among Women Undergoing Pelvic Reconstructive Surgery for Prolapse

Abstract: Objective The aim of this study was to determine if there is a difference in Pelvic Floor Disability Index Questionnaire (PFDI-20) scores between black and white women seeking surgical management for pelvic organ prolapse (POP). Methods A retrospective cohort study of 232 women who underwent pelvic reconstructive surgery with apical suspension for POP was performed. Demographic and clinical data were collected. All women completed the PFDI-20 and had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
6
0
4
Order By: Relevance
“…De acordo com Shek et al [17], mulheres AD possuem descenso de órgãos pélvicos significativamente maiores, inclusive a descida do colo da bexiga é maior, mesmo em repouso. Segundo Ford et al [20], essas diferenças etiológicas relacionadas a etnia, podem estar associadas à desigualdade socioeconômica, determinantes genéticos do POP e morfologia dos sistemas de suporte uretral. Quando se trata de lesões obstétricas, alguns dados indicam que o fator racial está diretamente ligado à ocorrência destas lesões [20].…”
Section: Características Dos Estudos Incluídosunclassified
See 3 more Smart Citations
“…De acordo com Shek et al [17], mulheres AD possuem descenso de órgãos pélvicos significativamente maiores, inclusive a descida do colo da bexiga é maior, mesmo em repouso. Segundo Ford et al [20], essas diferenças etiológicas relacionadas a etnia, podem estar associadas à desigualdade socioeconômica, determinantes genéticos do POP e morfologia dos sistemas de suporte uretral. Quando se trata de lesões obstétricas, alguns dados indicam que o fator racial está diretamente ligado à ocorrência destas lesões [20].…”
Section: Características Dos Estudos Incluídosunclassified
“…Segundo Ford et al [20], essas diferenças etiológicas relacionadas a etnia, podem estar associadas à desigualdade socioeconômica, determinantes genéticos do POP e morfologia dos sistemas de suporte uretral. Quando se trata de lesões obstétricas, alguns dados indicam que o fator racial está diretamente ligado à ocorrência destas lesões [20]. Encontra-se também casos em que o POP surge por conta de fatores hereditários para parentescos de primeiro grau, envolvendo genes pertencentes à biossíntese de colágeno e elastina [23].…”
Section: Características Dos Estudos Incluídosunclassified
See 2 more Smart Citations
“…9,10 Others have suggested that non-Latina White patients were more likely to have more advanced prolapse at the time of presentation compared with individuals of other races, while another study determined that Black patients presented with higher stages of prolapse when compared with non-Latina White patients. 5,11 Because there are limited data on objective prolapse severity among Latina patients, we sought to determine whether self-identifying Latina patients across 2 diverse hospital sites present with higher objective degrees of pelvic organ prolapse-as measured by overall POP-Q scores and leading edge of prolapse-compared with their non-Latina counterparts at the time of evaluation in a subspecialist clinic. We also sought to identify other characteristics that may be associated with higher degrees of prolapse at the time of initial presentation to a urogynecology clinic.…”
mentioning
confidence: 99%